2008
DOI: 10.17305/bjbms.2006.3116
|View full text |Cite
|
Sign up to set email alerts
|

Saliva and Serum Lithium Monitoring in Hospitalized Patients and Possibility to Replace Serum to Saliva

Abstract: The lithium ions concentration in human serum and saliva was determined using dry-slide technology Vitros 250 Analyser (Ortho Clinical Diagnostic) and atomic absorption spectrometry Perkin Elmer 403 (AAS). We analyzed lithium ions in 100 serum and saliva specimens of patients after oral administration of lithium carbonate (3 x 300 mg) Jadran, Galen Laboratory Rijeka. Saliva and blood were taken 2 and 12 hours after the last dose. At the same time lithium ions at samples of blood and saliva were determined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 2 publications
5
22
3
Order By: Relevance
“…While we found no association between time lapsed from last dose to blood collection, and either salivary lithium, serum lithium or saliva/serum lithium ratios, previous research by Serdarevic et al which compared salivary lithium and serum lithium correlations at 2-and 12-hours post-last dose, suggested that the saliva-serum correlation may be improved by collecting samples closer to the last dose [32] . Also, because of the known difference in lithium pharmacokinetics in saliva vs. serum [32,41] , the timing of the last dose is of critical importance. For inpatients, saliva measures could also be used to better optimize the timing of trough levels, as saliva sampling would not be restricted to a phlebotomist's schedule.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…While we found no association between time lapsed from last dose to blood collection, and either salivary lithium, serum lithium or saliva/serum lithium ratios, previous research by Serdarevic et al which compared salivary lithium and serum lithium correlations at 2-and 12-hours post-last dose, suggested that the saliva-serum correlation may be improved by collecting samples closer to the last dose [32] . Also, because of the known difference in lithium pharmacokinetics in saliva vs. serum [32,41] , the timing of the last dose is of critical importance. For inpatients, saliva measures could also be used to better optimize the timing of trough levels, as saliva sampling would not be restricted to a phlebotomist's schedule.…”
Section: Discussioncontrasting
confidence: 97%
“…Considering the overall literature, despite variations in methods of salivary lithium collection and quantification, the majority of previous studies have reported saliva/serum lithium correlations similar to that observed in our study [28][29][30][31][32][33] . This consistency in results across studies, as well as the stability in saliva/serum lithium ratios in most patients across time observed in our study, opens the door for the development and implementation of a point-of-care (POC) salivary lithium device.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…10(b-f) ). Clinically, lithium ions have been detected in the saliva of patients treated with lithium [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lithium is known to have narrow therapeutic range in the serum [28][29][30]. In a high dose, it could also be neurotoxic.…”
Section: Discussionmentioning
confidence: 99%